ROLE FAILURE CORRECTION OF 25(OH)D IN PATIENTS WITH POLYCYSTIC OVARY SYNDROME - M. V. Matveyeva; Yu. G. Samoylova; O. A. Oleynik; M. V. Koshmeleva; M. A. Rotkank (Бюллетень сибирской медицины, 2015)
Objective. To estimate the correction failure 25 (OH) D in patients with polycystic ovary syndrome.Material and Methods. The study involved 44 patients with polycystic ovary syndrome, aged 31.32 ± 5.05, who were randomly assigned to 2 groups: 1st – obtained coca biguanides and Kolekaltsiferol, second – combined oral contraceptive (combined hormonal ) and biguanides. The comparison group consisted of 22 healthy women matched for age and sex. Polycystic Ovarian Syndrome (PCOS) was verified on theОригинальные статьиБюллетень сибирской медицины, 2015, том 14, № 5, с. 47–53 53basis of diagnostic criteria ESHRE / ASRM (2012). 25 (OH) vitamin D was determined by enzyme-linked immunosorbent assay (ELISA ng/ml). Examined glucose and fasting insulin, HOMA index of insulin re-sistance. Depression was assessed using the Beck test. Statistical analysis – R-system.Results. The patients with PCOS defined by the expression deficit of 25 (OH) D, which is associated with hyperandrogenism, hyperglycemia, hyperinsulinemia, insulin resistance, as well as depression. Ad-mission kolekaltsiferola leads to improved glucose metabolism and manifestations of PCOS, and also significantly reduces the parameters of OT, OT / OB, depression.Conclusion. Failure correction of 25 (OH) D contributes to the improvement of metabolic and psycho-logical parameters of fertility.